Differences Of Saliva pH Towards The Compressive Strength Of Bulkfill Composite Resin - Badi Soerachman; Laeli Sabilah; Atia Nurul Sidiqa (Jurnal EduHealth, 2022)
Bulkfill composite resin has special qualities such as can be polymerized to 4 mm depth. One of the mechanical characteristics of bulkfill composite resins is high compressive strength. The compressive strength of restoration material is an indicator of successful restoration in the long-term. One factor that can affect the compressive strength in composite resins is the condition of the oral cavity. The oral cavity condition can be affected by the liquid in the oral cavity such as salivary pH. The compressive strength in composite resins is affected by the degradation process that is caused by changes in salivary pH. The purpose of this study was to find differences in artificial salivary pH toward the compressive strength in bulkfill composite resins. This study was divided into three groups, each group has 9 samples of bulk-filled composite resin in a disk shaped with 4 mm for diameter and 6 mm for the thickness based on ADA specification No.27/1993. All groups were soaked in artificial saliva at pH 4, 7, and 10 for 24 hours, and then the compressive strength was measured using UTM with a load of 250 kgf and speed of 0.5 mm/minute. The results of the tests were analyzed using Anova. Based on it, there is no difference between compressive strength in bulkfill composite resin on the immersion pH of artificial saliva 4, 7, and 10 with p-value of 0.546 (p>0.05). Moreover, there is no difference between the three-action maybe because of filler in bulkfill composite resin has more filler and UDMA rather than conventional composite resin. Therefore